(untitled) (International Journal of Physiotherapy, 2016)
Background: Frozen shoulder is a painful condition with gradual restriction of all planes of movement in the shoulder joint. The purpose of the present study is to evaluate the effect of Gong’s Mobilization versus Mulligan’s Mobilization on Shoulder pain and Shoulder Medial Rotation mobility in subjects with Frozen shoulder. Methods: An Experimental study design, 40 subjects with unilateral frozen shoulder were selected and randomized 20 subjects into each of two groups- Gong’s mobilization and Mulligan’s mobilization respectively. Gong’s group received the Gong’s mobilization technique with conventional therapy while Mulligan’s group received Mulligan’s mobilization along with conventional therapy. The duration of intervention was 5 treatment sessions per week for two weeks. Outcome measures such as shoulder medial rotation was measured using a Goniometer and pain was measured using a VAS scale before and after two weeks of intervention. Results: Analysis using Independent ‘t’ test and Mann Whitney U test found that there is statistically significant difference p<0.000 when pre to post interventions means were compared within the groups. When post intervention means were compared between the Gong’s and Mulligan’s groups there was no statistically significant difference in Active and Passive Range of Shoulder Medial Rotation but there was statistically significant difference in VAS when compared between the groups. Conclusion: It is concluded that both Gong’s mobilization with conventional therapy and Mulligan’s mobilization with conventional therapy are effective in improving Shoulder Medial Rotation Mobility in Frozen Shoulder. However Gong’s mobilization shown greater percentage of effect in reducing pain and Mulligan’s Mobilization shown greater percentage in improving ROM.